Assessing gender responsiveness of the Government-wide Monitoring and Evaluation System in South Africa - Dr Tirivanhu, Precious; Mr Jansen van Rensburg, Mandri (Development Southern Africa, 2017)
There is growing recognition of the critical role that National Monitoring and Evaluation Systems can play in achieving sustainable development through enhancing effectiveness, efficiency and sustainability of policies and programmes. The South African government legislated the Government-wide Monitoring and Evaluation System (GWMES) in 2009. The extent of gender responsiveness of the system has not been assessed yet gender mainstreaming ensures that gender needs, realities and issues are consistently and specifically considered in policies, programmes and projects. The study utilises data from document reviews and key informant interviews to assess gender. mainstreaming in the National Evaluation Policy (NEP) and the GWMES using a gender diagnostic matrix. Results indicate that the GWMES and NEP rank low in most gender-mainstreaming dimensions. However, the study concludes that existing policies and institutional frameworks if well supported by multiple stakeholders are conducive for effective gender mainstreaming within the GWMES in South Africa.
Keywords: gender mainstreaming; National Evaluation Policy (NEP); Government-wide Monitoring and Evaluation System (GWMES); South Africa